(untitled) (Experimental biology, 2024)
The flora of the Barsakelmes Nature Reserve represents a diverse world of plants adapted to the harsh conditions of the arid climate. Since its foundation in 1939, the Barsakelmes Nature Reserve has protected the ecosystems of the northern deserts of the Turanian Lowland in their natural state, being a standard of landscape structure and biodiversity. In 2006, the boundaries of the reserve increased after the drained seabed and the “Kaskakulan” cluster area were added to the territory. And in 2020, the “Delta” cluster area with an area of 2,300 hectares was added to the reserve, located at the confluence of the Syrdarya River and the Lesser Aral Sea. Thus, changes have occurred in the flora of the reserve. This article presents data that show changes in the taxonomic composition of the Barsakelmes flora depending on the detailed research and the expansion of the survey area after the addition of new...